Pemaknaan Simbolik pada Prosesi Kenduri Blang: Studi Kasus Gampong Ulee Gle Pidie Jaya - Anismar; Rukaiyah; Abdullah Akhyar Nasution (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2021)
This study aims to determine the symbolic meaning of the kenduri blang procession in Gampong Ulee Gle Pidie Jaya. Researchers used qualitative-descriptive research methods. Data collection techniques are observation, interview, and document study. The results showed that the community interpreted kenduri blang as a symbol of gratitude and asked for blessings from Allah so that the next crop was bountiful. Besides that, kenduri blang can also strengthen the relationship between people to stay united and respect each other. Kenduri blang was held in September, precisely before the beginning of descending into the fields. The community participates by donating funds to buy buffalo, spices, and other necessities needed when the event is held.